PhICl2-Mediated Regioselective and Electrophilic Oxythio/Selenocyanation of o-(1-Alkynyl)benzoates: Access to Biologically Active S/SeCN-Containing Isocoumarins - Tao, Shanqing; Huo, Aiwen; Gao, Yan; Zhang, Xiangyang; Yang, Jingyue; Du, Yunfei (Frontiers in Chemistry, 2022)
The application of PhICl2/NH4SCN and PhICl2/KSeCN reagent systems to the synthesis of the biologically active S/SeCN-containing isocoumarins via a process involving thio/selenocyanation, enabled by thio/selenocyanogen chloride generated in situ, followed with an intramolecular lactonization was realized. Gram-scale synthesis, further derivatization to access C4 thio/selenocyanated Xyridin A and anti-tumor activities of the obtained products highlight the potential use of this method.